خيارات التمويل المتاحة للمؤسسة في النظام المالي الاسلامي دراسة حالة القرض الاستهلاكي بنك البركة وكالة عنابة - ميلود اونيسي; وليد شعباني (My University, 2021)
Islamic banks have witnessed a remarkable development and have been able to prove their worth through their performance in the banking market. Algeria and like other countries, has decided to try this experience through creating a bank who follow the rules of an Islamic bank. In this research, we were able to shed lights on how Islamic banks provide financing. The characteristics of institutions and the nature of their transformational needs, loans and consumer financing offered by Islamic banks are an important source of financing, as well as its attractive way image in financing institutions and various economic activities. Al Baraka is the witness of the great success that Islamic banks achieved. Our study aims to give details of how actually financing through Islamic banks works. ..................................................................... وقد شهدت البنوك الإسلامية تطوراً ملحوظاً واستطاعت أن تثبت جدارتها من خلال أدائها في السوق المصرفية. الجزائر، كغيرها من الدول، قررت تجربة هذه التجربة من خلال إنشاء بنك يتبع قواعد البنك الإسلامي. وقد تمكنا في هذا البحث من تسليط الضوء على كيفية قيام البنوك الإسلامية بتقديم التمويل. إن خصائص المؤسسات وطبيعة احتياجاتها التحويلية، تشكل القروض والتمويل الاستهلاكي التي تقدمها البنوك الإسلامية مصدرا هاما للتمويل، فضلا عن صورتها الجذابة في مؤسسات التمويل والأنشطة الاقتصادية المختلفة. وبنك البركة شاهد على النجاح الكبير الذي حققته البنوك الإسلامية. تهدف دراستنا إلى تقديم تفاصيل حول كيفية عمل التمويل الفعلي من خلال البنوك الإسلامية.